Daylighting of buildings: Theoretical methodological proposal for the characterization and evaluation of spaces - Rosalinda González; Lesvia Pérez; Gaudy Bravo; Eduardo González; Elizabeth Tsoi (Revista Técnica de la Facultad de Ingeniería, 2010)
The objective of this work is to make a theorical methodological proposal for the daylighting characterization and evaluation of spaces, in buildings under the real sky condition; these was developed to be applied in the evaluation of Bioclimatic House Prototype VBP-1, designed for Maracaibo -Venezuela's city (100 40.5' north latitude). This Proposal was divided in two parts: the first, directed to define a process for the characterization (existent situation) in which were described the procedures of measure of quantitative aspects (external illuminance, interior illuminance, reflectance and transmitance of the surfaces), identifying and classifying parameters presents on each one of them and the second part, direct to define a process for the evaluation (ideal situation) with the values recommended by standards, which subsequently permit to establish comparisons between existing and recommended values. Like result of this methodology, was design a series of register forms for take data, which facilitate the daylighting characterization and evaluation of each space.